PENINGKATKAN PENGETAHUAN MASYARAKAT LANSIA DALAM PENCEGAHAN DAN PENANGANAN OSTEOARTHRITIS DI KEC. SIANTAR BARAT - Muliati, Muliati; Marolop Parlindungan Napitu,; Isa Harpika Br. Ginting,; Ilham Irwansyah, (Nusantara Hasana Journal, 2023)
Osteoarthritis is a degenerative disease commonly experienced by the elderly and can reduce quality of life due to pain and limited mobility. Lack of public knowledge regarding the prevention and treatment of osteoarthritis is a contributing factor to the worsening condition. This community service activity aims to increase the knowledge of elderly people in West Siantar District regarding the prevention and treatment of osteoarthritis. The methods used included health education, interactive discussions, and demonstrations of simple physical exercises. The results showed an increase in participants' understanding of the risk factors, symptoms, and self-management methods for osteoarthritis. This activity is expected to help elderly people maintain joint health and improve their quality of life.